Monotransitive Constructions in Seereer - Ngom, Marie (Afrikanistik-Aegyptologie-online, 2014)
As far as transitivity is concerned, Seereer verbs can be divided into three major types (with several subtypes for each): Strictly intransitive, strictly transitive and ambitransive or labile verbs. This paper will focus on one class of strictly transitive verbs namely monotransitive verbs including no voice mechanism. In section 2, I describe the syntactic diagnosis of transitivity, in section3, the coding properties of arguments, in section 4, I discuss the different groups within the monotransitive class, then I finally will analyse non-coded alternations in section 5.
Keywords: Afrikanistentag 2012; Flagging; Seereer; Tagungsband Afrikanistentag; monotransitive verbs; passivization; verbes monotransitifs